IMPLEMENTATION OF QUANTUM TEACHING METHODS TO KNOW THE EFFECT OF THE ABILITY OF WRITING DRAMA STUDENTS OF SMP NEGERI 3 PRINGSEWU IN 2016 - Anggraeni, Leni; Puspita, Dian (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2019)
Teaching about writing drama scripts is part of teaching Indonesian. The aim of teaching drama scriptwriting at SMP / MTs is to emphasize the ability to write drama scripts in accordance with the rules of writing drama scripts. This is the hope of every educator and a junior high school student. This study aims to investigate the effect of using the Quantum Teaching method on the ability to write drama scripts in class VIII semester I SMP Negeri 3 Pringsewu in 2016. The method used is an experimental method which can be interpreted as a research method used to find the effect of certain treatments on others. under controlled conditions. The experimental design used is a true experimental design in the form of pretest-posttest Control Group Design because in this form the researcher can control all the variables that affect the course of the research. Meanwhile, the different test on the ability to write drama scripts uses the Quantum Teaching method between the experimental class and the control class using the paired sample t-test. From the results of data analysis using the paired sample t-test, the t-test value is 2.556. 2,000 or 2,556> 2,000. This shows the influence of the use of the Quantum Teaching method on the ability to write drama scripts